The application of categorical regression to model the exposure-response relationship of copper excess and deficiency - Chambers, Andrea (University of Ottawa (Canada), 2010)
There is a need to define an exposure-response curve for both copper excess and deficiency to assist in defining the acceptable range of oral intake. A copper exposure-response database has been developed where response data has been assigned to ordinal severity scores. A generalized linear model was used to estimate the probability of response associated with dose, duration and severity. The exposure-response model is defined to account for differences in animal species, route of exposure and age. The exposure-response curves for copper excess and copper deficiency have defined an optimal intake level of 2.0 mg Cu/day and an acceptable range of oral intake between 1.8 and 3.1 mg Cu/day. These results suggest that current recommendations for copper intake including the recommended dietary intake (0.9 mg/day) and the tolerable upper intake level (10 mg/day) may not protect the population from responses that might occur outside the limits of the homeostatic range.
Keywords: Health Sciences, Toxicology.; Health Sciences, Epidemiology.